Development of a collaborative interorganizational system : a case study - Wu, Jianli. (2008)
Interorganizational system (IOS) is defined as information technology-based systems that link two or more organizations, and facilitate the exchange of products, services and/or information. It has been adopted with a varying degree of success. Implementing IOS is a complex and expensive process. This project aims to provide better understanding of the issues faced by companies in adopting IOS>